A ÁREA DE PRESERVAÇÃO PERMANENTE DA TRILHA ECOLÓGICA DO RIO POTIRIBÚ, NO PARQUE DE EXPOSIÇÕES WANDERLEY AGOSTINHO BURMANN, IJUÍ, RS, BRASIL - Massafra, Patricia S.; Gass, Sidnei L. B. (Salão do Conhecimento, 2013)
Resumo